A Review of Pedicled Perforator Flaps for Reconstruction of the Soft Tissue Defects of the Leg and Foot - Low, O-Wern; Sebastin, Sandeep J.; Cheah, Andre E. J. (Indian Journal of Plastic Surgery, 2019)
Lower extremity soft tissue defects frequently result from high-energy trauma or oncological resection. The lack of suitable muscle flap options for the distal leg and foot makes defects in these locations especially challenging to reconstruct and free tissue transfer is commonly used. Another option that has become more popular in the past two decades are pedicled perforator flaps. Based on a thorough literature review and the authors’ experience on leg perforator flaps for over a decade, this article presents a historical review, the anatomical basis of common perforator flaps of the leg and foot, patient selection, wound selection, perforator selection, flap design, surgical techniques, refinements, and postoperative care. A review of the clinical outcomes and complications of these flaps was also performed and was noted to be comparable to the outcomes of free tissue transfer with significantly lower total flap failure rate. It is hoped that this review will assist surgeons in the formulation of a comprehensive step-by-step guide in performing pedicled perforator flap reconstruction of the lower extremity.
Keywords: foot defects; leg defects; pedicled flap; perforator flap; propeller flap